Cultivating a Culture of Literacy and Addressing the Psychological Impact on Students with Migrant Worker Parents - Maria Goreti Rini Kristiantari; Nice Maylani Asril; Ketut Herya Darma Utami (International Journal of Community Service Learning, 2026)
Several obstacles hinder the development of a culture of literacy, including a lack of school facilities and teachers' skills. These challenges are further compounded for students whose parents are Indonesian Migrant Workers (PMI), who are vulnerable to psychological impacts such as anxiety, depression, and low emotional support due to the absence of parents. This community service activity aims to analyze the increasing level of partner empowerment in the field of literacy culture and the psychological impact on students. This activity focuses on community service activities. Subjects involved 50 teachers. Data collection methods used included questionnaires and interviews with students and teachers. The instrument used was a questionnaire sheet. Data analysis was conducted using descriptive and inferential statistical techniques. This activity demonstrated that implementing a community-based literacy program and teacher training to address students' psychological issues were effective in improving literacy culture and students' emotional well-being. It was concluded that students participating in the literacy program showed increased reading interest and academic performance. At the same time, teacher-provided psychological support helped mitigate the emotional impact of having PMI parents. Schools in other regions can adopt this intervention model to holistically improve the quality of education and student well-being.